Intensification of Sprinkler-Irrigated Corn Production - F. R. Lamm (Kansas Agricultural Experiment Station Research Reports, 2022)
This corn intensification study was conducted under sprinkler irrigation from 2020 to 2021 at the Kansas State University Northwest Research-Extension Center near Colby, KS. Two corn hybrids (Pioneer 1197 and Pioneer 1089) were grown with advanced fertilization at three plant densities (42,000, 38,000, and 34,000 plants/a) using three irrigation levels (115, 100, or 85% of calculated well-watered ET minus rain). As anticipated, there was no additional need for irrigation above normal amounts (100% of ET - Rain), giving further evidence that crop intensification is possible without negatively affecting water resource use. Yields were excellent in both years, averaging 227 bu/a in 2020 and 306 bu/a in 2021. Both corn hybrids yielded well and overall the greater plant density gave slightly greater yields. Crop water productivity was maximized at an irrigation level of 85% of ET - Rain, with the Pioneer 1197 hybrid, and with a plant density of 42,000 plants/a.
Keywords: crop intensification; irrigated corn; sprinkler irrigation; water productivity